High flow nasal therapy versus noninvasive ventilation as initial ventilatory strategy in COPD exacerbation: a multicenter non-inferiority randomized trial - Andrea Cortegiani; Federico Longhini; Fabiana Madotto; Paolo Groff; Raffaele Scala; Claudia Crimi; Annalisa Carlucci; Andrea Bruni; Eugenio Garofalo; Santi Maurizio Raineri; Roberto Tonelli; Vittoria Comellini; et al. (Critical Care, 2020)
Abstract Background The efficacy and safety of high flow nasal therapy (HFNT) in patients with acute hypercapnic exacerbation of chronic obstructive pulmonary disease (AECOPD) are unclear. Our aim was to evaluate the short-term effect of HFNT versus NIV in patients with mild-to-moderate AECOPD, with the hypothesis that HFNT is non-inferior to NIV on CO2 clearance after 2 h of treatment. Methods We performed a multicenter, non-inferiority randomized trial comparing HFNT and noninvasive ventilation (NIV) in nine centers in Italy. Patients were eligible if presented with mild-to-moderate AECOPD (arterial pH 7.25–7.35, PaCO2 ≥ 55 mmHg before ventilator support). Primary endpoint was the mean difference of PaCO2 from baseline to 2 h (non-inferiority margin 10 mmHg) in the per-protocol analysis. Main secondary endpoints were non-inferiority of HFNT to NIV in reducing PaCO2 at 6 h in the per-protocol and intention-to-treat analysis and rate of treatment changes. Results Seventy-nine patients were analyzed (80 patients randomized). Mean differences for PaCO2 reduction from baseline to 2 h were − 6.8 mmHg (± 8.7) in the HFNT and − 9.5 mmHg (± 8.5) in the NIV group (p = 0.404). By 6 h, 32% of patients (13 out of 40) in the HFNT group switched to NIV and one to invasive ventilation. HFNT was statistically non-inferior to NIV since the 95% confidence interval (CI) upper boundary of absolute difference in mean PaCO2 reduction did not reach the non-inferiority margin of 10 mmHg (absolute difference 2.7 mmHg; 1-sided 95% CI 6.1; p = 0.0003). Both treatments had a significant effect on PaCO2 reductions over time, and trends were similar between groups. Similar results were found in both per-protocol at 6 h and intention-to-treat analysis. Conclusions HFNT was statistically non-inferior to NIV as initial ventilatory support in decreasing PaCO2 after 2 h of treatment in patients with mild-to-moderate AECOPD, considering a non-inferiority margin of 10 mmHg. However, 32% of patients receiving HFNT required NIV by 6 h. Further trials with superiority design should evaluate efficacy toward stronger patient-related outcomes and safety of HFNT in AECOPD. Trial registration: The study was prospectively registered on December 12, 2017, in ClinicalTrials.gov (NCT03370666).